Development of Students Worksheets Based on Local Wisdom of the Kampar Community for Social Studies Learning of Elementary School - Yuyun Santika; Otang Kurniaman; Munjiatun Munjiatun; Zufriady Zufriady (AL-ISHLAH: Jurnal Pendidikan, 2023)
Local wisdom is part of the wealth that is owned by the Indonesian people in every region, including the Kampar Regency. Local wisdom must be preserved through education by integrating Kampar local wisdom with social studies learning that uses teaching materials in the form of students worksheet (LKPD) in delivering material in learning for fourth-grade students of elementary schoolin Riau. This study aims to produce LKPD products based on the local wisdom of the Kampar community in social studies learning for grade IV elementary schools that are valid, appropriate, and effective. This research uses the type of RD research with a 4D development model, which consists of 4 stages, namely define, design, develop, and disseminate. Based on the results of local wisdom-based research, the developed LKPD shows valid, proper and effective LKPD with very valid media expert validation results of 84.64%, very valid material experts with a validation value of 82.29%, and 87 linguists. 5% with very valid category. It was said to be feasible based on the results of the teacher's response of 81.59% in the very feasible category, the response of 2 students in the one to one stage was 85.76% in the feasible category, and the response of 10 students in the small group test stage was 91.69% in the very feasible category. This LKPD is effective based on the results of the pretest-posttest which is measured by the N-Gain test obtaining a value of 0.6 in the medium category. This shows that the LKPD products based on the local wisdom of the Kampar people are valid, feasible and effective.